The Rolling Head Legend among Algonquians - Granzberg, Gary (Anthropologica, 2022)
An analysis based upon structural, archetypal and emic theory reveals that the Rolling Head legend among Algonquians supports the ideology of balance and oneness with nature and opposes the ideology of separation, manipulation and domination of nature. The analysis shows that the legends of Iyas and Trickster’s Race with Rock are variants of the Rolling Head legend and that Earth Diver is an inversion. The analysis also links the legend to a wider body of mythic material which may be subsumed under the nomenclature of Mother Goddess legends.